The Urgency of Education Supervision in Improving Teacher Professionalism at SMK Rinjani Praya - nur hamiyetun (al-Hikmah : Jurnal Studi Islam, 2021)
The importance of the role of educational supervision in improving the professionalism of teachers at SMK Rinjani Praya has been attempted to achieve maximum results. The implementation of educational supervision at SMK Rinjani Praya is motivated by conditions where teachers still have difficulties, conventional teaching methods, and lack of mastery in using learning media that already exist at SMK Rinjani Praya. Supervision is carried out by the principal who is represented by the Deputy Principal, which aims to improve the professionalism of teachers at SMK Rinjani Praya as a whole through various supervision techniques. The final goal that is expected to be achieved with supervision is the creation of an effective and relevant teaching and learning process through increasing capabilities and the availability of supporting factors.This type of research uses qualitative methodological methods as a research procedure that produces descriptive data as a study of awareness from a person's main perspective. Researchers in the phenomenological view try to understand the meaning of events and their relation to people in certain situations.The results of the discussion The implementation of supervision by the principal at SMK Rinjani Praya has been categorized as very good with a percentage of 83.25% based on the achievements of aspects of planning, implementation, evaluation, and supervision.The professionalism of building engineering teachers at SMK Rinjani Praya has been categorized as good with an achievement percentage of 80.20% based on the achievements of pedagogical, personality, social, and professional aspects.